The Anthropological Concept in Chronicles and its Implications to the Eschatological Remnant - Neto, Joaquim Azevedo (Revista Hermenêutica (descontinuada), 2014)
Abstract The Chronicler masterfully weaves the biblical view of human nature into the fabric of the remnant motif. This understanding of humanity could well be a useful example for God’s end-time covenant community to define its own anthropological perception and its self-identity as remnant, for there is a noticeable parallel between both communities: the postexilic and the eschatological one. Two lessons from Chronicles help us to perceive the importance of this subject to God’s end-time community of faith. The first lesson is that anthropology should be defined by God’s revelation and not by a secular or social view of anthropology. Secondly, self-identity of the remnant is a natural fruit of God’s grace, operating through His chosen institution: in the old covenant the temple and its rituals, in the new covenant the church and its mission. Keyowrds: Anthropological Concept; Chronicle; Eschatological Remnant Resumo O Cronista magistralmente tece a visão bíblica da natureza humana no tecido do motivo remanescente. Esta compreensão da humanidade poderia muito bem ser um exemplo útil para a comunidade da aliança do fim dos tempos para definir a sua própria percepção antropológica e sua autoidentidade como remanescente, pois há um paralelo notável entre as duas comunidades: a pós-exílica e escatológica. Duas lições de Crônicas nos ajudam a perceber a importância do tema para a comunidade de fé do fim dos tempos. A primeira lição é que a antropologia deve ser definida pela revelação de Deus e não por uma visão secular ou social da antropologia. Em segundo lugar, autoidentidade do remanescente é um fruto natural da graça de Deus, operando através de Sua instituição escolhida: na antiga aliança, o templo e seus rituais, na nova aliança, a Igreja e sua missão. Palavras-chave: Conceito Antropológico; Crônica; Remanescente Escatológico.